2018
DOI: 10.1016/j.neuron.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Light Prior to Eye Opening Promotes Retinal Waves and Eye-Specific Segregation

Abstract: Retinal waves are bursts of correlated activity that occur prior to eye-opening and provide a critical source of activity that drives the refinement of retinofugal projections. Retinal waves are thought to be initiated spontaneously with their spatiotemporal features dictated by immature neural circuits. Here we demonstrate that, during the second postnatal week in mice, changes in light intensity dictate where and when a subset of retinal waves are triggered via activation of conventional photoreceptors. Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 46 publications
2
53
0
Order By: Relevance
“…increases the frequency of those waves (Tiriac et al, 2018). Our model predicts that this would expedite the emergence of LHCs and that orientation-specific LHCs would be observed earlier than in a normal condition (Fig.…”
mentioning
confidence: 67%
“…increases the frequency of those waves (Tiriac et al, 2018). Our model predicts that this would expedite the emergence of LHCs and that orientation-specific LHCs would be observed earlier than in a normal condition (Fig.…”
mentioning
confidence: 67%
“…photoreceptor dependent) (Fig. 3B), although a recent study reported light-dependent photoreceptor activity even prior to eye opening (P8-P10) (Tiriac et al, 2018). In contrast, light-responsive activity of intrinsically photosensitive melanopsin ganglion cells occurs from embryonic development (E16.5) into adulthood (Fig.…”
Section: The Relationship Between Neuronal and Glial Specification Anmentioning
confidence: 83%
“…Defective synaptic pruning of RGC inputs to the relay neurons in the dLGN leads to incomplete eye‐specific segregation (Schafer et al , ; Chung et al , ; Vainchtein et al , ). To investigate the effects of microglial GPR56 deficiency on eye‐specific segregation, we performed anterograde tracing of RGC inputs with two different colored fluorescent CTB (Fig A) and quantified the extent of segregation with a threshold‐independent method as described (Torborg & Feller, ; Tiriac et al , ). We observed a significantly larger overlap at P10 in CKO mice (Fig EV5A and B), persisting to P30 (Fig B–D) when eye‐specific segregation should be completed, suggesting improper organization of retinogeniculate projections sustained throughout development.…”
Section: Resultsmentioning
confidence: 99%